Diário e memória em Abdias de Cyro dos Anjos - Martins, Angélica Pereira (2017)
This dissertation analyzes the Diary in Abdias, second novel of Cyro dos Anjos. We write about life and work of the writer, which was born in Minas Gerais State, Brazil, primarily; in the following chapters, we present the novel structure, even as its review and plot. The studies of Diana Klinger, Blanchot, Barthes, Foucault and Lejeunne base the first chapter that deals with the concept of self-writing and analyzes the writing of Abdias character´s Diary emphasizing that the narrator uses an intimate and confessional writing to get closer to reader. Ecléa Bosi's texts and her reads of Bergson’s theory compose the second chapter that elucidate the concept of memory and analyze the protagonist, Abdias, memorialistic issue, illustrated by the moment that he goes through the classrooms of Colégio das Ursulinas (School of Ursulinas) as a Literature Teacher, which is the turning point of his loving life. Oziris Borges Filho, Osman Lins and Yi-Fu Tuan works comprehend the notion of space and its function in the novel´s plot. The third chapter works with the text of Philippe Lejeune, “How do diaries end?”, at least, and analyzes how Abdias finish his writings. The self- writing, memory and space are elements present in the book and highlight the protagonist’s relationship with living and writing. After all, Abdias believed that often “reading or writing was more important than living”.